Genomic Surveillance and Phylodynamic Analyses Reveal the Emergence of Novel Mutations and Co-mutation Patterns Within SARS-CoV-2 Variants Prevalent in India - Biswas, Nupur; Mallick, Priyanka; Maity, Sujay Krishna; Bhowmik, Debaleena; Mitra, Arpita Ghosh; Saha, Soumen; Roy, Aviral; Chakrabarti, Partha; Paul, Sandip; Chakrabarti, Saikat (Frontiers in Microbiology, 2021)
Identifications of the genomic diversity and the phylodynamic profiles of the prevalent variants are critical to understand the evolution and spread of the SARS-CoV-2 variants. We performed whole-genome sequencing of 54 SARS-CoV-2 variants collected from COVID-19 patients in Kolkata, West Bengal during August to October 2020. Phylogeographic and phylodynamic analyses were performed using these 54 and other sequences from India and abroad available in the GISAID database. We estimated the clade dynamics of the Indian variants and compared the clade specific mutations and the co-mutation patterns across states and union territories of India over the time course. Frequent mutations and co-mutations observed within the major clades across time periods do not show much overlap, indicating emergence of newer mutations in the viral population prevailing in the country. Further, we explored the possible association of specific mutations and co-mutations with the infection outcomes manifested within Indian patients.